THE EFFECT OF OCCUPATIONAL HEALTH COMPETENCE AND SAFETY (K3) ON EMPLOYEE PERFORMANCE - Saffitri Indriani; Agi Syarif Hidayat; Sunimah Sunimah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research is to determine the influence of competence and application of occupational health safety (K3) performance of production employees at PT Findora Internusa Cirebon. The research method used is a quantitative research method. The population in this study is the workforce of PT Findora Internusa Cirebon. The technique used in sampling is saturated sample, where the total population used as a sample is 76 respondents. The data collection method uses questionnaires, while the method in this study uses multiple linear regression analysis. Based on the results of the study, it can be concluded that: 1) Competence has a significant effect on performance with a significance value of 0.005, 2) K3 has a significant effect on performance with a significance value of 0.000, and 3) Competence and K3 can be used as predictors of growth or decrease in performance because they have a significance value of 0.000.